A review of the process physics and material screening methods for polymer powder bed fusion additive manufacturing. (June 2019) - Chatham, Camden A.; Long, Timothy E.; Williams, Christopher B.
Graphical abstract: Abstract: Powder bed fusion (PBF) is one of seven different classes of additive manufacturing (AM) technologies identified by ASTM and ISO. In polymer PBF, an infra-red energy source selectively fuses powder particles layer-by-layer into a three-dimensional structure. This enables the production of parts without the use of a mold, which is useful for prototyping and low-volume production. The early research in polymer PBF has focused largely on exploring the expanded design space afforded by the technology and modeling the heat transfer during fabrication. These are aspects that emphasize the manufacturing process and resultant quality in a material agnostic manner. Early investigations into structure-process-property relationships focused on the industrially dominant polyamide family. Only recently has research been conducted towards expanding the PBF material portfolio beyond nylon-12 and its composites. Guiding this research is the knowledge gained from studying the behavior of polyamides in PBF, which resulted in pervasive guidelines for material screening and process parameter development in polymer PBF, including the concepts of a "stable sintering region" and utilizing the "energy melt ratio" to set machine parameters. However, these guidelines are largely empirical and disproportionately focus on process parameter effects on the mechanical properties of the printed parts, instead of the intrinsic polymer properties and first principles of polymer science and engineering. This review categorically compiles the PBF AM literature by the three process sub-functions: powder recoating, energy input, and coalescence and cooling. The literature outlining the governing physics, structure-property-processing relationships enabling printing, and the process-structure-property relationships enabling targeted final part properties are discussed within each sub-function. Establishing these polymer-manufacturing relationships, both for printability and for final part property prediction, is important to aid in the identification and adaptation of existing polymers, and development of novel polymers, for PBF AM.